2021
DOI: 10.1111/add.15455
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐Specific Risk Profiles for Suicide Among Persons with Substance Use Disorders in Denmark

Abstract: Background and Aims Persons with substance use disorders (SUDs) are at elevated risk of suicide death. We identified novel risk factors and interactions that predict suicide among men and women with SUD using machine learning. Design Case–cohort study. Setting Denmark. Participants The sample was restricted to persons with their first SUD diagnosis during 1995 to 2015. Cases were persons who died by suicide in Denmark during 1995 to 2015 (n = 2774) and the comparison subcohort was a 5% random sample of individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 55 publications
0
23
0
2
Order By: Relevance
“…As noted earlier, studies indicate that persons with TBI who engage in LTOT are at an increased risk for overdose (nonfatal and fatal) and suicide attempt 8,28–31. A recent study that used machine learning to reveal sex-specific predictors of suicide among persons with substance use disorders in Denmark revealed that prior poisoning (ie, overdose) was among the most important predictors of suicide death, particularly among women, and that this risk could extend for many years after the poisoning 54. Investigation of this dynamics among persons with TBI is warranted, as persons with TBI are at an elevated risk for suicide,33,34,55 and prior overdose may help identify those at even a greater risk of suicide.…”
mentioning
confidence: 99%
“…As noted earlier, studies indicate that persons with TBI who engage in LTOT are at an increased risk for overdose (nonfatal and fatal) and suicide attempt 8,28–31. A recent study that used machine learning to reveal sex-specific predictors of suicide among persons with substance use disorders in Denmark revealed that prior poisoning (ie, overdose) was among the most important predictors of suicide death, particularly among women, and that this risk could extend for many years after the poisoning 54. Investigation of this dynamics among persons with TBI is warranted, as persons with TBI are at an elevated risk for suicide,33,34,55 and prior overdose may help identify those at even a greater risk of suicide.…”
mentioning
confidence: 99%
“…In women, interaction between recurrent major depression and other characteristics (e.g., poisoning, low income). Adams et al, [ 73 ] 15,953 patients with SUD (5745/10208) SUD Not specified Classification tree, RF (10-folds CV) 2563 social and demographic information, mental and physical health diagnoses, surgeries, medications, and poisonings Suicide attempts Classification tree AUC: 0.75 RF AUC: 0.77 Among men, most important variables: reaction to severe stress, adjustment disorders, drugs used, age 30+, and prior poisoning. Among women, most important predictors: prior poisonings and reaction to stress and adjustment disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, very few studies (n=5) ( 30 , 31 , 36 , 43 , 88 ) stratified their analyses by sex. This represents a significant gap in the literature, as the gender paradox in suicide (i.e., women tend to attempt suicide more often, while men tend to die by suicide more often) is well-known.…”
Section: Discussionmentioning
confidence: 99%